Does the Implementation of Green Banking Affect the Profitability of Islamic Banks in Indonesia? - Salsabila Dwiayu Fajriah; Ririn Riani; Miftakhus Surur (Universitas Darussalam Gontor, 2023)
Green banking has been at the peak of popularity over the last few decades. The green movement in the banking industry is triggered by the acceleration of global climate change due to environmental damage. Green banking is an important component of Islamic banking which serves as the basis for environmental protection and also enhances the reputation of the organization. This study investigates the impact of implementing green banking on Islamic banking profitability in Indonesia from 2016 to 2020 by using a sample of nine Islamic Commercial Banks (BUS). To evaluate the relationship among variables, Panel Data Analysis is employed. The findings depict that the implementation of Green Banking had no significant impact on the profitability of Islamic Commercial Banks during the study period. This study shows that the implementation of green banking incurs various costs, such as compliance costs, which will have an impact on profitability. Therefore, the transition to green banking demands a strong commitment to the